A Majestic Anthropology?: Indwelling and Shared Agency in Early Lutheran Theology - Kohli, Candace L. (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2023)
Sixteenth-century Christological debates sought to clarify the philosophical implications of the hypostatic union thesis formulated at Chalcedon. The genus maiesticatum, in particular, permitted that Christ's created human nature could be said to possess divine attributes and powers. Other systematic regions like theological anthropology were implicated in this concept as well; the elevation of Christ's human nature provided a conceptual framework for understanding the way divine indwelling might elevate human moral capacities in the elect. Medieval Scholastics after Lombard sought to clarify what type of relation indwelling might be. Was it a hypostatic union as in Christology or something else? At the start of the sixteenth-century, Protestant reformers inherited this question. Their engagement with it demonstrates the systematic implications of Christological metaphysics and clarifies conceptual continuities and shifts that occurred across this historical moment of reform.